Pandemi Covid-19 Sebagai Peristiwa Dunia: Analisis Teologi Profetik Kitab Yoel 1-2 Terhadap Krisis Global Kontemporer - La'ia, Dewi (STT Kristus Alfa Omega, 2025)
This study analyzes contemporary natural events through the theological perspective of the Book of Joel 1-2, particularly the concept of the